Defeating Merchants of Doubt: Subjective certainty and self-affirmation ameliorate attitude polarization via partisan motivated reasoning. (October 2020) - Han, Jiyoung; Kim, Yungwook
Informed by uncertainty–identity theory, this study tested the polarizing effect of partisan-led politicization of science and ways to combat it. Using a national sample of South Koreans ( N  = 840), our online experiment found that when partisan elites, as opposed to scientists (or civic activists), spearheaded politicization, attitude polarization emerged via partisan motivated reasoning. Such polarizing effects of party cues did not persist when subjective certainty and self-affirmation enhanced the level of certainty partisans felt about their surroundings and themselves. These patterns proved consistent across multiple scientific issues, including climate change, genetically modified foods, and algae blooms. The implications of the findings are discussed in light of how to attenuate the polarizing effect of partisan-led politicization through the lens of social identity approaches. Given that this study provides one of the first pieces of evidence on the topic outside the Western context, the advantages of using a South Korean sample are noted.